Sri Lanka : Report on the Observance of Standards and Codes (ROSC) Data Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report is a summary assessment of Sri Lanka's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS), complemented by an in-depth assessment of the elements of data quality that underlie the national accounts, prices, government finance, monetary, and balance-of-payments statistics. Sri Lanka has made good progress in meeting most of the SDDS specifications on coverage, periodicity, and timeliness of data categories. Shortcomings exist in the access, integrity, and quality dimensions compared with the SDDS. All agencies demonstrate professionalism and are generally transparent in their practices and policies.